Hubungan Lama Pemakaian Alat Kontrasepsi Suntik 3 Bulan Dengan Gangguan Menstruasi Pada Akseptor KB Suntik 3 Bulan di Puskesmas Melak Kalimantan Timur Tahun 2023 - Rika Husniati; Adelina Sembiring; Mastaida Tambun (Lembaga Pengembangan Kinerja Dosen, 2024)
Three month injectable birth control is an alternative used to prevent pregnancy by releasing the hormone progestin into the blood vessels which works by stopping the release of egg cells into the uterus, thus preventing the fertilization process from occurring. Menstrual changes experienced by women taking DepoProvera begin in the form of unpredictable irregular bleeding and spotting that lasts for seven days or more or heavy bleeding during the first few months of Depo-Provera use. The aim of this study was to determine the relationship between the length of use of 3-month injectable contraceptives and menstrual disorders in 3-month injectable contraceptive acceptors at the Melak District Health Center. West Kutai, East Kalimantan in 2023.he type of research carried out was Descriptive Analytical with a cross sectional approach, the sample in the study was 35 people using a Random Sampling System. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square The results of the tabulation research show a relationship between the duration of using injectable contraceptives for 3 months and menstrual disorders in 3-month injectable contraceptive acceptors at the Melak District Health Center. West Kutai, East Kalimantan in 2023 with a p-value = 0.049. So Ho is rejected and Ha is accepted, which means there is a relationship between the length of use of 3-month injectable contraceptives and menstrual disorders in 3-month injectable contraceptive acceptors at the Melak District Health Center. West Kutai, East Kalimantan in 2023. Conclusion: Family planning acceptors can choose the right contraceptive method. Family planning acceptors can tell midwives or health workers about the various types of contraceptives before choosing the contraceptive method. Always monitor changes in side effects so that if there are complaints they can be addressed immediately.